Ensino Médio - curso normal: desafios e perspectivas do estágio curricular para formação docente - Pinheiro, Ana Paula (2019)
The present work reflects on the initial and continuous formation of the students / students teachers, of the High School - Normal Course, highlighting it as initial formation of teachers. I emphasize the relevance of continuing training during the period of the curricular internship and analyze the methodological difficulties encountered by the trainees during the internship, demystifying the relation between theory and practice, that is, the internship would be the moment of put theory into practice. The research was carried out within the horizon of the quali-quanti approach, of an exploratory nature, adopting the methodology of documentary research and action research, having as an instrument of data collection the narratives; written record about the methodological difficulties encountered during the completion of the curricular internship. The subjects of this research were eleven students from the first-semester-oriented class of 2018, from the State Institute Ernesto Ferreira Maia, located in the municipality of Fontoura Xavier - RS. At the same time, I developed the intervention project entitled "Continuing education in the curricular stage of the normal course: the pedagogical practice as a source of research and re-signification", through the continuous training related to the topics listed in the narrative register by the students / the trainees. At the end of this intervention project, the empirical material was categorized and analyzed, from which I produced the diagnosis and elaborated a proposal containing guiding pedagogic guidelines to qualify the High School - Normal Course of the Institute. For the mapping thematic, I chose two events recognized as a source of research and dialogues in the area of education, ENDIPE and ANPEd, in the search for a collection on the descriptors of this research. I produced a brief historical tour of the Normal Course at the intermediate level, as well as the legal explanation about the Normal Course and the compulsory curricular traineeship. I spoke with the following authors: initial training and continuing education Nóvoa (1999), Perrenoud (2002), Libâneo (2017), Sartori (2013), Chimentão (2009), Candau (1997), Fávero and Tonieto (2010). On the historical aspects of the Normal course Nogaro (2002), Tanuri (2000), Saviani (2005) and to refer to the quali-quanti research proposal in this study, Minayo (1992), Thiollent (1988), Santos 1995), Bardin (1977), Paiva (2017), approaching aspects of the internship: Pimenta e Lima (2012), Cavalcanti (1993), and to elucidate pedagogical methodologies I worked with the ideas of Nericé (1987), Anastasiuou (2001) ), Ferreira et al (2012) and Farias (2011). I recognize that by linking continuous training to initial training, it enables us to understand that theory is the foundation that allows us to analyze situations in practice and to produce new knowledge. The product of this study is configured as: "guiding pedagogical indicatives", constructed from the narratives and the suggestions of the subjects of this research, that point to some methodological changes, that must be rethought for the continued formation of the teacher trainers of the Course of the Institute.